IDENTIFIKASI MALARIA DENGAN PROGRAM INDOOR RESIDUAL SPRAYING (IRS) WILAYAH KERJA PUSKESMAS SILAU LAUT KABUPATEN ASAHAN - Ice Ratnalela Siregar; Mardan Ginting (Poltekkes Kemenkes Medan, 2023)
Malaria is an infectious disease caused by the Plasmodium parasite that lives and reproduces in human red blood cells. This disease is naturally transmitted through the bite of a female Anopheles mosquito. Manifestation of the malaria elimination program using the Artemisinin Combination Therapy (ACT) method, prevention of malaria transmission using LLIN (Long Lasting Insecticidal Net) mosquito nets, and Indoor Residual Spraying (IRS). The purpose of this study was to determine the characteristics of malaria cases based on age, sex, microscopic examination, type of plasmodium and knowledge of respondents. pre test and post test in the IRS program in the working area of Silau Laut Health Center, Asahan Regency. The benefits of this research are expected to provide information about the incidence of malaria with the Indoor Residual Spraying (IRS) program so that it can increase community efforts to prevent malaria in the work area of the Silau Laut Health Center, Asahan Regency. The type and design of this research is Quasi Experiment with Pre and Post Test design without control.. The results of the Pre-Test knowledge of respondents in the medium category were 50 respondents (50%). The results of Post Test knowledge in the medium category increased to 60 respondents (60%). There is an effect of the intervention program on IRS on the knowledge of pre-test and post-test respondents in the work area of the Silau Laut Health Center, Asahan Regency. The Asahan District Health Office needs to conduct operational research on appropriate alternative interventions to increase the coverage of ACT treatment in endemic areas. The Health Office. More intensify all malaria prevention and eradication efforts in the work area of the Silau Laut Health Center in Asahan Regency. Vector eradication with indoor implementation Residual Spraying on a regular basis, Installing wire netting on the ventilation holes of the house. Use of insecticide-treated mosquito nets to prevent mosquito bites at night.